SOSIO-BUDAYA PANGAN SUKU BADUY - Ali Khomsan; Winati Wigna (Food and Nutrition Society of Indonesia, 2009)
Banten Province in Indonesia has a traditional tribe called Baduy. Baduy tribe is still maintaining their traditions against modernization. The objectives of this research were to analyze socio-economic and demographic characteristics of Baduy people, socio-cultural and ecological aspects of Baduy community, and food availability of Baduy people. This research is an explorative and descriptive study on the socio-cultural aspects of food system. The data required to meet the research objectives were collected through a direct interview and discussion with respondents as well as a direct observation at the location of respondents. A sample size of 338 households was drawn from the population. The allocation of sample was 303 for Outer Baduy, 10 for Inner Baduy and 25 for Moslem Baduy. To obtain the data on the cultural aspects, history and socio aspect of food, in-depth interviews was conducted with 19 key persons. The study was last for 12 months. The rice production of Baduy community to supply its basic need is generally insufficient; as a result, they have to purchase rice from outside. In addition, not all rice they produce can be consumed because some of it is for the needs of traditional ceremonies. As much as 25 % of the production is sold or given to their neighbors who are lack of rice, 25 % is sent for their neighbors’ feast and for traditional ceremonies (for the elderly people, Jaro, and Puun), and the 50 % is stored in the rice barn for their daily consumption. Only poor households use their rice for their daily consumption. Baduy community usually purchases their foodstuffs at the market, the shop, or from the vegetable vendor who sells from one village to another. If Baduy people need rice and other foodstuffs, they usually go to another village to fulfill their needs.